1
$\begingroup$

I am trying to get an expression for this integral

$$ \int_0^1 \mathrm{d}x \dfrac{x^6\log(1-x)} {\sqrt{\left( x^3 - \lambda(x-1)\right)^3}} $$

with $ \lambda \ll1$.

I know this integral has no solution in terms of elementary functions so I am trying to see the behaviour in $\lambda$ when $\lambda \rightarrow 0$. I can't make a Taylor expansion for the square root in the denominator, because when $x \approx 0$, $\lambda$ and $x$ become comparable, and the expansion doesn't converge.

What I have tried is to split the integral in two intervals $[0,\lambda]$ and $[\lambda,1]$ and then expand for $x/\lambda \ll 1$ for the first interval and for $\lambda/ x \ll 1$ for the second one. However it seems I don't obtain the good behaviour. In fact, I'm not sure of the validity of this.

Any hint about how to get the good behaviour in $\lambda$?

Thanks in advance!

$\endgroup$
1
$\begingroup$

I am not sure I understand. When $\lambda=0$ the numerator is $-x^7$ since $\log(1-x)\sim -x$ and the denominator only $x^{9/2}$ so the integral converges. Can't you just use Lebesgue dominated convergence theorem?

EDIT OK, I understand now. Call $$ g(\lambda)=\int_{0}^{1}\frac{x^{6}\log(1-x)}{(x^{3}-\lambda(x-1))^{3/2}}dx $$ and

$$ f(x,\lambda)=\frac{x^{6}\log(1-x)}{(x^{3}-\lambda(x-1))^{3/2}}. $$ Then $$ \frac{\partial f}{\partial\lambda}(x,\lambda)=\frac{3}{2}\frac{(x-1)x^{6}% \log(1-x)}{\left( x^{3}+\lambda(1-x)\right) ^{\frac{5}{2}}}% $$ and so since $0\leq x^{3}\leq x^{3}+\lambda(1-x)$, \begin{align*} \left\vert \frac{\partial f}{\partial\lambda}(x,\lambda)\right\vert & =\frac{3}{2}\frac{(1-x)x^{6}|\log(1-x)|}{\left( x^{3}+\lambda(1-x)\right) ^{\frac{5}{2}}}\leq\frac{3}{2}\frac{(1-x)x^{6}|\log(1-x)|}{x^{\frac{15}{2}}% }\\ & \sim\frac{3}{2}x^{7-^{\frac{15}{2}}}=\frac{3}{2}x^{-^{\frac{1}{2}}}% \end{align*} near $x=0$, which is integrable (near $x=1$ there is no problem since $t\log t\to 0$), where we used the fact that $\log(1-x)\sim-x$ near $x=0$. So you can differentiate under the integral sign to find that $$ g^{\prime}(0)=\int_{0}^{1}\frac{3}{2}\frac{(x-1)x^{6}\log(1-x)}{\left( x^{3}\right) ^{\frac{5}{2}}}dx $$ and so$$ g(\lambda)=\int_{0}^{1}\frac{x^{6}\log(1-x)}{(x^{3})^{3/2}}dx+\lambda\int% _{0}^{1}\frac{3}{2}\frac{(x-1)x^{6}\log(1-x)}{\left( x^{3}\right) ^{\frac {5}{2}}}dx+o(\lambda) $$

$\endgroup$
2
  • $\begingroup$ Similarly the derivative of the integral with respect to $\lambda$ converges at $\lambda = 0$. You run into problems in trying to get higher orders than that. $\endgroup$ – Robert Israel Jul 12 '17 at 22:48
  • $\begingroup$ $\lambda$ is not zero, but small. At the end, I would like to have a function of $\lambda$. The difficult part, I think, is that here I can't just apply Taylor's formula for $\lambda$ small and then integrate, since for $x$ small there is an important contribution to the integral $\endgroup$ – ASM Jul 13 '17 at 11:27

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.